LITERATUR REVIEW: Pengaruh Penggunaan Gadget Terhadap Kesehatan Mental Pelajar Di Masa Pandemi Covid-19 - Dwi Fikri, Nayli Arista (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
The number of students using gadgets during the pandemic has increased very rapidly. The use has an impact on mental health from the emotional, psychological, and social aspects. Objective: to review the literature on the effect of using gadgets on students' mental health during the COVID-19 pandemic. Method: The method used in this literature review is to select a topic, then determine keywords to search for journals using English and Indonesian through several databases, including Google Scholar, PubMed, and Science Direct. Results: This literature review shows that the use of gadgets has a positive and negative impact on students' mental health. The positive impact that arises is that students continue to communicate with friends even during the pandemic. As for the negative impact, students become lazy to study, get angry easily, and lack socialization because they play gadgets more often than playing with friends around them. Conclusion: The use of gadgets during the pandemic can improve the mental health of children and adolescents, but their use must be considered and limited so as not to cause addiction.